O envelhecimento como princípio direcionador no percurso dos personagens em Reflexões de um liquidificador, de André Klotzel - Caiuby, Marília Lefèvre (2021)
The objective of this dissertation is to research the concept of aging as portrayed in the film Reflexões de um Liquidificador, by André Klotzel (2010). We have tried to map out the choices and creation processes employed in the work. The corpus of the research is Klotzel’s film and the interviews about the making of process. The film was chosen by its original way of portraying the aging question. We see it as a hybrid type of work that alternates between “real” and surreal situations, consisting of metaphorical and non-linear narrative. We have reflected about the construction and articulation of the central elements to the film and their results in relation to the process of aging. The research is based on the study of creation processes by Cecília Almeida Salles and its connection to the concept of complexity by Edgar Morin. We have also sought theoretical support in the areas of cultural studies, literature and psychoanalysis. The research, therefore, has an interdisciplinary character